Operational Efficiency, Capital Adequacy, and Profitability: A Case Study of Central Java’s Regional Development Bank - Jatmiko, Bambang (Lembaga Riset Ilmiah, 2025)
This study aims to analyse the impact of BOPO (Operational Efficiency Ratio), LDR (Loan to Deposit Ratio), NPL (Non-Performing Loans), and KPMM (Capital Adequacy Ratio) on ROA (Return on Assets) in the Regional Development Bank of Central Java Province. Utilizing quarterly data published by the Financial Services Authority (OJK) from Q1 2017 to Q4 2024, the study employs a multiple regression approach to assess the relationships among variables. The empirical findings reveal that both BOPO and LDR exert a significant negative effect on ROA, indicating that higher operational inefficiencies and excessive lending relative to deposits diminish bank profitability. In contrast, KPMM shows a significant positive impact, suggesting that stronger capital adequacy enhances financial performance. NPL, however, is found to have no statistically significant effect on ROA. These results underline the importance of prudent cost management, balanced liquidity strategies, and robust capital buffers in improving bank profitability. The study recommends that policymakers strengthen regulations to enhance capital adequacy and promote operational efficiency, which in turn supports the resilience and growth of regional banking institutions. These insights contribute to the formulation of more effective economic policies in the regional banking sector, fostering financial stability and regional economic development.